Coping with climate change : national summit proceedings - Bierbaum, Rosina M., 1952-; Brown, Daniel G.; McAlpine, Jan L.; University of Michigan. School of Natural Resources and Environment; National Summit on Coping with Climate Change (2007 : Ann Arbor, MI) (Ann Arbor, MI : University of Michigan, School of Natural Resources and Environment)
Includes bibliographical references.